Quantitative evaluation to efficacy and safety of therapies for psoriasis: A network meta-analysis. Issue 1 (March 2018) - Lv, Jingjing; Zhou, Dongmei; Wang, Yan; Zhao, Jingxia; Chen, Zhaoxia; Zhang, Jinchao; Di, Tingting; Hu, Jing; Li, Bo; Li, Ping; Huang, Feng
Therapies treating psoriasis can be categorized into five classes according to their mechanism: anti-metabolites (AM), anti-interleukin-12/23 agents (anti-IL12/23), anti-interleukin-17 agents (anti-IL17), anti-T-cell agent (ANT), and anti-tumor necrosis factor-α agent (anti-TNF-α). This network meta-analysis (NMA) aimed to give a quantitative and systemic evaluation of safety and efficacy for the five kinds of therapies mentioned above. Odds ratios and mean differences were calculated to evaluate binary and continuous outcomes, respectively. Forest plots were conducted to show the performance of pair-wise comparison of above therapies in each outcome, and surface under the cumulative ranking curves was given to evaluate the relative ranking of above therapies in each outcome. Node splitting was conducted to evaluate the consistency between direct and indirect evidence. Direct comparisons from 65 studies (32, 352 patients) were included in this NMA. Our results showed an excellent efficacy of anti-IL12/23 and anti-IL17. However, these two therapies and anti-TNF-α were revealed to have a high possibility to cause adverse effects (AEs) such as infections. Additionally, node splitting showed that no inconsistency appeared between the direct and indirect comparisons. Anti-IL12/23 was the most recommended therapy according to this NMA. Anti-IL17 had similar efficacy to anti-IL12/23 but should be applied with caution since it has poor performance in safety outcomes.